Private Infrastructure : Private Activity Fell by 30 Percent in 1999 - Izaguirre, Ada Karina; Rao, Geetha (World Bank, Washington, DC, 2012)
This note, which draws on the World Bank's Private Participation in Infrastructure (PPI) database, provides an overview of recent trends in infrastructure projects with private participation in developing countries. Three main trends have emerged during the past decade. Private activity in infrastructure grew dramatically between 1990 and 1997, but declined because of the financial crises of 1998-99. Most developing countries have some private activity in infrastructure, but Latin America, and East Asia dominate investments. It is suggested that private infrastructure activity in developing economies will revive as they recover form the economic crisis of the late 1990s, and the fundamental reasons for long-term private activity, - increasing demand for infrastructure, sector inefficiencies, and public budget constraints - will continue.